Peningkatan Kemampuan Membaca Pemahaman Melalui Metode Survey, Question, Read, Recity, Review (SQ3R) pada Siswa Kelas VI UPT SPF Sudirman 1 Makassar - Magfirah Safitrah; Tarman A Arief; Akbar Avicenna (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to improve the reading comprehension skills of Class VIB students at UPT SPF SDN Sudirman 1 Makassar through the implementation of the Survey, Question, Read, Recite, Review (SQ3R) method. The background of the study is the low learning outcomes in Indonesian language subjects, particularly in reading comprehension. Out of 32 students, only 20 reached the Minimum Mastery Criteria (KKM) score of 75. This research uses a Classroom Action Research (CAR) approach conducted in two cycles. Each cycle includes the stages of planning, action, observation, and reflection. The instruments used in this study were observation sheets, written tests, and documentation. The results showed a significant improvement in students’ reading comprehension abilities. The average score increased from 70.63 in the first cycle to a higher score in the second cycle, with more students achieving the KKM. Additionally, students showed greater participation and enthusiasm during the learning process after the SQ3R method was applied. These findings indicate that the SQ3R method is effective in enhancing reading comprehension and can be used as an alternative learning strategy in teaching Indonesian language at the elementary school level.